Fé no Surué : análise de produção de documentário sobre um festejo na Amazônia - Dias Filho, Claudio Aurélio Leal (2022)
The present work analyzed the production process of the documentary Fé no Surué about the cult/festival of São Surué and the attempts to create shared procedures as a form of a decolonial intervention from the audiovisual. This process allowed a better understanding of the celebration and possible interpretations from the author's place of production and his interaction with the participants of the celebration and worship of São Surué. The analysis crosses academic theoretical references from different areas of knowledge such as History, Anthropology, Cinema, Sociology and contemporary cultural studies, enabling an interdisciplinary look at the theme that produces another narrative about the festivities. Community demands such as memory preservation and the return of audiovisual material produced to the community are considered in the thesis as well as the celebration itself and the reflection of ethical issues of academic and audiovisual production. In this interweaving, there is a set of analyzed narratives about São Surué, whether that of the community, the documentary as well as the academic work.